Environmentally compatible bioconjugated gold nanoparticles as efficient contrast agents for colorectal cancer cell imaging - Araújo, Aurigena Antunes de (2018)
In this study we show, for the first time, that gold nanoparticles (AuNPs) synthesized by a simple, inexpensive, and environmentally-correct method can be easily conjugated with the antibodies anti-β-catenin and anti-E-cadherin to specifically target colorectal carcinoma cells. The antibody/AuNPs conjugates were then successfully applied for imaging cancerous cells with fluorescence confocal microscopy. The AuNPs as well as the conjugates were very stable in high-salinity medium, a pre-requisite for application in physiological-like environments. Fluorescence results suggest that conjugation was achieved by direct adsorption of antibodies on the AuNPs surface. Finally, compared with a standard method of cell staining, our method is less laborious and the preparation time (from immobilization of cells onto glass cover slips until observation by confocal microscopy) decreased from 27 h to about 1 h, which makes the method eligible for colorectal cancer diagnostic.